Optimized preparation of micro-block CPAM by response surface methodology and evaluation of dewatering performance. Issue 1 (22nd December 2016) - Li, Xiang; Zheng, Huaili; Gao, Baoyu; Sun, Yongjun; Tang, Xiaomin; Xu, Bincheng
Abstract : Micro-block cationic polyacrylamide (P(AM-MAPTAC)) was synthesized through UV-initiated template copolymerization and characterized by FTIR, 1 H NMR, SEM and TG/DSC analyses. Abstract : Micro-block cationic polyacrylamide (P(AM-MAPTAC)) was synthesized through UV-initiated template copolymerization and characterized by FTIR, 1 H NMR, SEM and TG/DSC analyses. Furthermore, the main influence factors of the preparation process were optimized through Box–Behnken experiment design and Respond Surface Method (RSM). The maximum intrinsic viscosity of micro-block CPAM was 13.223 dL g −1 under the optimum synthesis conditions. The dewatering performance of micro-block CPAM was evaluated taking activated sludge collected from a dyeing mill as the processing object. Results showed that the micro-block CPAM exhibited excellent dewatering performance. At a 30 mg L −1 dosage of micro-block CPAM, the residual turbidity, filter cake moisture content, specific resistance to filtration and chemical oxygen demand removal rate reached 4.47 NTU, 72.2%, 5.47 (10 12 m kg −1 ) and 79.2%, respectively. Dewatering tests not only demonstrated the superiority of micro-block P(AM-MAPTAC) synthesized by UV-initiated template copolymerization over that synthesized by traditional methods but also demonstrated that increasing the molecular weight can further enhance the dewatering performance of flocculants.